HUBUNGAN INFARK MIOKARD AKUT ( IMA ) YANG DIRAWAT INAP DENGAN HIPERTENSI DI RSUD DR. H. ABDULMOELOEK PROVINSI LAMPUNG TAHUN 2014 & 2015 - Rina Kriswiatiny; Zulhafis Mandala; Melisa Efendy (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2019)
Hypertension is the increase in systolic blood pressure over 140 mmHg and diastolicblood pressure over 90 mmHg in two measurements within an interval of five minutesin a state of rest or quiet enough. Increased blood pressure in the long term (persistent ) can cause organ damage one of which is the heart ( coronary heartdisease ) if not detected early and treated adequately. The aim of this study is to knowrelations between acute myocardial infarction and hypertension in patients who arehospitalized in the Hospital Dr. H. Abdul Moeloek 2014 and 2015. The researchmethod used in this research is the method of analytic research with cross sectionalstudy on the samples used were 111 respondents in patient wards heart disease in Dr.H. Abdul Moeloek Hospital Lampung Province, 2014 & 2015. It has been foundSTEMI with grade 1 hypertension were 58 respondents (52.3%) higher than thesecond degree as much as 11 respondents (9.9%), NSTEMI with grade 1 hypertensionwere 19 respondents (17.1%) lower compared to the second degree as much as 23respondents (20.7%). Based on the statistical test obtained by value p = 0.000 (OR =6.383, 95% CI = 2.632 to 15.478). It can be concluded that there is a significantrelationship between acute myocardial infarction and hypertension.